Ultrasonographic Evaluation of Solitary Thyroid Nodule with Histopathological Comparison (Bangladesh Journal of Otorhinolaryngology, 2020)
Background: Thyroid gland is the largest gland of the body which secretes thyroid hormones named T3 & T4. Incidence of solitary thyroid nodule is common in Bangladesh.Objectives: To validate the ultrasonography evaluation of solitary thyroid nodule comparing with histopathological diagnosis.Methodology: This cross sectional study enrolled 75 patients of age range between 14 to 72 years during July 2016 to June 2018 and the study was carried out in the department of Radiology & Imaging of Ultrasonography evaluation was finally compared with histopathological diagnosis which was considered as gold standard.Results: Among 75 patients are included in this study the age ranged between 14 to 72 years. Majority of the patients 37 (49.3%) were found between 31 to 40 years. 65 (86.3%) were female & 10 (13.3%) were male. All patients were presents with thyroid swelling. In USG findings Microcalcifications were present 9 (12%) in benign & 5(6.7%) in malignant cases. Presence of Halo were in all benign cases 14 (18.7%). Comet tail sign were in 5 (6.7%) in benign & 3 (4%) in malignant cases. Histological nodular goiter were 57 (76%), Follicular adenoma 8 (10.7%), Thyroditis 5 (6.7%) and Papillary carcinoma 4 (5.3%), Follicular Carcinoma 1 (1.3%).Conclusion: This cross sectional study was carried out with an aim to determine the usefulness of ultrasonogram diagnosis of solitary thyroid nodule compared with histopathology findings. As the validity test results are higher, it can be concluded that the ultrasonogram is a useful diagnostic modality in the evaluation of solitary thyroid nodule.Bangladesh J Otorhinolaryngol; October 2019; 25(2): 76-84